Associations of long-term exposure to ambient nitrogen dioxide with indicators of diabetes and dyslipidemia in China: A nationwide analysis. (April 2021) - Zhang, Qingli; Liu, Cong; Wang, Yafeng; Gong, Jinquan; Wang, Gewei; Ge, Wenzhen; Chen, Renjie; Meng, Xia; Zhao, Yaohui; Kan, Haidong
Abstract: Background: The associations between ambient NO2 and diabetes and dyslipidemia have been controversial, and data is especially lacking in developing countries. Objective: This study aimed to assess the associations of long-term exposure to NO2 with diabetes and dyslipidemia in China. Methods: We conducted a cross-sectional study including 13, 013 participants from the China Health and Retirement Longitudinal Study (CHRLS). The annual average concentrations of NO2 were estimated based on the residential addresses of participants. We applied logistic regression models to evaluate the associations of NO2 with diabetes and dyslipidemia, and linear regression models to assess the associations with blood biomarkers. Results: A total of 1933 diabetes cases (14.85%) and 1935 (14.87%) dyslipidemia cases were identified. Significant associations were observed between NO2 and risk of diabetes and dyslipidemia independent of PM2.5 and O3 . For an interquartile range (IQR) increase in NO2 (12.39 μg/m 3 ), we observed a 13% [odds ratio (OR): 1.13; 95% confidence interval (CI): 1.01, 1.26] increased risk of diabetes, 1.48% (95%CI: 0.51%, 2.46%) increase in glucose, 0.74% (95%CI: 0.19%, 1.29%) increase in glycosylated hemoglobin (HbA1c), 17% (OR: 1.17; 95% CI: 1.05, 1.31) increased risk of dyslipidemia, 4.62% (95%CI: 2.49%, 6.79%) increase in triglyceride, and a decrease of 2.96% (95%CI: 2.13%, 3.79%) in high-density lipoprotein. The associations of NO2 with glucose disorders were stronger among smokers. Conclusions: Our study indicated long-term exposure to NO2 might contribute to the development of diabetes and dyslipidemia, and the associations were potentially independent of O3 and PM2.5 . Highlights: Long-term exposure to NO2 was associated with diabetes and dyslipidemia. Associations of NO2 with blood glucose and lipid were independent of O3 and PM2.5 . The associations between NO2 and glucose disorders were stronger among smokers.